PEMBELAJARAN INTEGRATIF BAHASA INDONESIA DAN SBDP MELALUI PROYEK POSTER HEMAT ENERGI PADA SISWA KELAS III SDN KUPU 02 - Roasih, Roasih; Mulyono, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to design an integrative learning model combining Indonesian Language and Arts for third-grade students at SDN Kupu 02 Wanasari, Brebes through the project “Energy-Saving Posters and Environmental Stories” within the Merdeka Curriculum framework. The learning problem identified is the separation between language and arts learning, low literacy and expressive skills, limited differentiation practices, and the lack of authentic assessment. The purpose of this study is to enhance students’ literacy, visual creativity, collaboration, and environmental awareness through contextual, project-based, and differentiated instruction. The methodology employed is descriptive qualitative, utilizing data from classroom observations, student products, teacher interviews, and relevant literature. The learning design applies Project Based Learning (PjBL), collaborative learning, contextual teaching, and differentiation of content, process, and product. The expected outcomes include improved reading comprehension and writing of persuasive messages, increased creativity in producing visual posters, strengthened communication and collaboration skills, and the development of environmental responsibility aligned with the Profile of Pancasila Students. The results show that integrative and project-based learning enables students to express ideas through multimodal texts, work effectively in groups, and demonstrate higher engagement in language and arts activities. Furthermore, authentic assessment provides a more comprehensive understanding of students’ cognitive, affective, and psychomotor development. This study concludes that collaborative and differentiated learning designs significantly enrich meaningful learning experiences and support the development of literacy, creativity, and ecological awareness in primary school students.